Effects of Air Pollution on the Immune Response of Residents Around Benda Sub-District, Tangerang - Siti Mimah Rohimah; Nita Noriko (Universitas Al Azhar Indonesia, 2025)
Air pollution around Benda Sub-district, Tangerang has become a critical environmental issue due to the high intensity of traffic transportation and industrial activities that contribute to the emission of harmful gases. Prolonged exposure to air pollutants poses significant health risks, including adverse effects on the human immune system, particularly for communities residing. This study aims to examine the immune response, specifically leukocyte differentials (neutrophils, eosinophils, monocytes, basophils, lymphocytes) and C-Reactive Protein in individuals aged 25–35 years living in densely populated settlements. A cross-sectional approach was employed involving 24 volunteer participants, accompanied by air quality measurements at the sampling location, including TSP, SO₂, NO₂, Pb, CO, Ox, NMHC, PM₁₀, and PM₂.₅. The results highlighted the high MCV levels in all participants could causing the basic inflammatory response in the body. Furthermore, this study revealed that air pollution exposure indirectly affects the immune system.